Utilization of rapid antigen tests for screening SARS-CoV-2 prior to dental treatment - Pittayapat, Pisha; Trachoo, Vorapat; Jirachoksopon, Chongpean; Udom, Kalaya; Champakerdsap, Chunya; Rungrojwittayakul, Oraphan; Kamolratanakul, Paksinee; Linsuwanont, Pairoj; Boonprakong, Lawan; Koottathape, Natthavoot; Pungpapong, Vitara; Osathanon, Thanaphum; et al. (Frontiers in Oral Health, 2022)
Potential aerosols containing SARS-CoV-2 viral particles can be generated during dental treatment. Hence, patient’s triage is essential to prevent the spreading of SARS-CoV-2 in dental clinical settings. The present study described the use of rapid antigen tests for SARS-CoV-2 prior to dental treatment in an academic dental clinical setting in Thailand during our third pandemic wave. The opinions of dental personnel toward the use of rapid antigen test screening prior to dental treatment was also assessed. During August 25 to October 3, 2021, dental patients who were expected to receive aerosols generated by dental procedures were requested to screen for SARS-CoV-2 using a rapid antigen test prior to their treatment. A total of 7,618 cases completed the screening process and there was an average was 212 positive cases per day. Only five cases (0.07%) were positive SARS-CoV-2 with the rapid antigen screening tests. All positive cases exhibited mild symptoms. Experienced dental personnel frequently and consistently agreed with the use of the rapid antigen test for SARS-CoV-2 screening since they feel safer during their patient treatment. However, the implement of rapid antigen test for SARS-CoV-2 might add the additional steps and take time during dental appointment. The rapid antigen test could detect the infected individual prior to dental treatment. However, the specificity of rapid antigen tests for SARS-CoV-2 must be taken into account for consideration as screening process prior to dental treatment. The enhanced infection control protocols in dental treatment must be consistently implemented.